2016
DOI: 10.3847/2041-8205/822/2/l31
|View full text |Cite
|
Sign up to set email alerts
|

A Rich Globular Cluster System in Dragonfly 17: Are Ultra-Diffuse Galaxies Pure Stellar Halos?*

Abstract: Observations of nearby galaxy clusters at low surface brightness have identified galaxies with low luminosities, but sizes as large as L å galaxies, leading them to be dubbed "ultra-diffuse galaxies" (UDGs). The survival of UDGs in dense environments like the Coma cluster suggests that UDGs could reside in much more massive dark halos. We report the detection of a substantial population of globular clusters (GCs) around a Coma UDG, Dragonfly 17 (DF17). We find that DF17 has a high GC specific frequency of S N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
141
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(166 citation statements)
references
References 38 publications
23
141
2
Order By: Relevance
“…HR17 used weak lensing results to connect their measured stellar masses to halo masses (M 200 ) and virial radii (R 200 (Peng et al 2016), and assign approximate virial radii of 130 and 175 kpc respectively. The four most massive galaxies in our sample lack halo masses and virial radii.…”
Section: Resultsmentioning
confidence: 99%
“…HR17 used weak lensing results to connect their measured stellar masses to halo masses (M 200 ) and virial radii (R 200 (Peng et al 2016), and assign approximate virial radii of 130 and 175 kpc respectively. The four most massive galaxies in our sample lack halo masses and virial radii.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the recent discovery of "ultra-diffuse" galaxies (UDGs) in large galaxy clusters (van Dokkum et al 2015;Koda et al 2015;Mihos et al 2015;Muñoz et al 2015;Martínez-Delgado et al 2016) have been proposed to represent failed L * galaxies with deep potentials relative to their stellar masses. Little is known about their respective GC systems, but recent work has indicated that they may have high SN 30 with as many as dozens of GCs (Beasley & Trujillo 2016;Peng & Lim 2016;van Dokkum et al 2016). These works find that UDGs are likely to host primarily blue GC populations more similar to dwarfs than giants, although with only one UDG GC system studied so far, few general conclusions can be drawn.…”
Section: The Extreme Halo Of Ngc 5128 and Its Gc Systemmentioning
confidence: 99%
“…Using the abundance and kinematics of globular clusters around two UDGs, VCC 1287 and DF17, and Beasley & Trujillo (2016) estimated the corresponding dynamical masses to be around m vir ∼ (8 ± 4) × 10 10 M and m vir ∼ (9 ± 2) × 10 10 M , respectively, similar to that of the typical dwarf galaxies. Using the relation between the mass of the globular cluster system and the halo mass (Harris, Harris & Alessi 2013;Harris, Harris & Hudson 2015), Peng & Sungsoon (2016) also inferred the total mass of DF17 to be (9.3 ± 4.7) × 10 10 M ; Amorisco, Monachesi & White (2016) estimated the dynamical masses of 54 Coma UDGs to be lower than 1.3 × 10 11 M . Román & Trujillo (2017a) also found that the distribution of UDGs around A168 is similar to the normal dwarfs, but significantly different from the distribution of massive galaxies with masses similar to the Milky Way.…”
Section: Introductionmentioning
confidence: 99%